2012
DOI: 10.1021/ef201884r
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Rate Enhancements for Coal Direct Chemical Looping Combustion with an Iron Oxide Oxygen Carrier

Abstract: Chemical looping combustion (CLC) has been suggested as an energetically efficient approach for coal combustion with CO 2 sequestration. An iron oxide oxygen carrier is an attractive option because of its low cost and environmental compatibility. However, the low reactivity between iron oxide and coal is a challenge for its application. In this paper, the effects of the C/Fe 2 O 3 molar ratio and alkali carbonate addition on the reduction rate of coal char with an Fe 2 O 3 oxygen carrier and the feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Results showed that the carbon conversion was improved by the addition of Ca. Yu et al (2012) investigated the effects of alkali carbonates addition on the reduction rate of coal char with Fe 2 O 3 oxygen carrier, and the feasibility of coal char direct CLC with alkali carbonate impregnated Fe 2 O 3 oxygen carrier. It was found that the high reduction rate of coal char with Fe 2 O 3 oxygen carrier can be achieved with alkali carbonates addition.…”
Section: Possible Catalytic Mechanismmentioning
confidence: 99%
“…Results showed that the carbon conversion was improved by the addition of Ca. Yu et al (2012) investigated the effects of alkali carbonates addition on the reduction rate of coal char with Fe 2 O 3 oxygen carrier, and the feasibility of coal char direct CLC with alkali carbonate impregnated Fe 2 O 3 oxygen carrier. It was found that the high reduction rate of coal char with Fe 2 O 3 oxygen carrier can be achieved with alkali carbonates addition.…”
Section: Possible Catalytic Mechanismmentioning
confidence: 99%
“…These mixtures as oxygen carrier created a synergistic effect on enhancing the fuel conversion due to the inevitable contact among char, catalysts and oxygen carrier. The other way is to develop a combined Fe-based oxygen carrier with carbonates [16,17] and cement [18,19]. Commonly, these combined oxygen carriers involve the creation of new compounds, which promote the reaction between gaseous products and oxygen carrier [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The solid inventory of a CLC process is expected to be significantly decreased if the high reaction rate and high OTC of oxygen carrier are simultaneously satisfied. Our previous research indicated that the reduction rate of iron oxide oxygen carrier of coal direct CLC could be remarkably enhanced by the addition of alkali metal carbonates (high reactivity); meanwhile, the Fe 2 O 3 can be reduced to an oxidation state of FeO/Fe (high OTC), suggesting that catalytic CLC was an effective method of coal combustion with a low solid inventory [14]. Even though there are some researches focusing on the effects of alkali metal on iron-based oxygen carrier, the catalytic mechanism has not been addressed in more detail, especially in the following aspects: (1) how the alkali metal initially loaded on oxygen carrier catalyzes the char gasification; (2) the catalytic effect of reduced iron oxide itself on char gasification in the presence of alkali metal addition; and (3) the maintained catalytic effect in the multicycle operation.…”
Section: Introductionmentioning
confidence: 99%